URGENSI KRIMINALISASI BAGI PEKERJA SEKS KOMERSIAL - Yurista Ardien Adhipradana; Wiwik Afifah (Gapenas Publisher, 2023)
Prostitution s a phenomenon that s familiar to society. Prostitution s considered a crime against decency or morals. There are 3 parties nvolved n this practice of prostitution, namely, pimps, commercial sex workers who are victims of TIP or commercial sex workers who sell themselves. The purpose of this research s to find out what s the urgency of criminalizing Commercial Sex Workers. the factors that cause the crime of prostitution, the majority of the problem lies n economic factors which are nfluenced by one's ncome or needs, especially the difficulties for women to meet their needs especially women who do not have skills so that competitiveness n the world of work s very low, then coupled with the occurrence of a pandemic which has made fewer and fewer jobs and competition n the world of work s even tighter, this has made them choose shortcuts by colonizing themselves (their bodies) n order to survive. n addition, social factors also nfluence, especially environmental conditions, environmental conditions, and one's education. This study uses a normative juridical method using a statutory approach, a conceptual approach, and a comparative approach. The results of this study can be concluded that basically criminalizing Commercial Sex Workers s not possible because Commercial Sex Workers are basically victims so Commercial Sex Workers should not be criminalized but n rehabilitation